(untitled) (Revista Internacional de Formação de Professores, 2024)
The present study aimed to discuss the precariousness of teaching work in the area of ​​Special Education. The research is qualitative in nature, based on bibliographical analysis, the results showed that the debate regarding the precariousness of teaching work has been widely discussed in society and in educational spaces, given that neoliberal policies are on the rise. These policies make the withdrawal movement or its reduction in the execution of policies become increasingly stronger, resulting in the Minimum State. When it comes to Special Education, we conclude that the teacher’s work becomes even more precarious and devalued, because with business logic, this professional is required to take on numerous functions, without having adequate and quality initial and continuing training.